Chromaticity of Certain 2-Connected Graphs - Lau, Gee Choon (2003)
Since the introduction of the concepts of chromatically unique graphs and chromatically equivalent graphs, many families of such graphs have been obtained. In this thesis, we continue with the search of families of chromatically unique graphs and chromatically equivalent graphs. In Chapter 1, we define the concept of graph colouring, the associated chromatic polynomial and some properties of a chromatic polynomial. We also give some necessary conditions for graphs that are chromatically unique or chromatically equivalent. Chapter 2 deals with the chromatic classes of certain existing 2-connected (n, n + 1,)-graphs for z = 0, 1, 2 and 3. Many families of chromatically unique graphs and chromatically equivalent graphs of these classes have been obtained. At the end of the chapter, we re-determine the chromaticity of two families of 2-connected (n, n + 3)-graphs with at least two triangles. Our main results in this thesis are presented in Chapters 3, 4 and 5. In Chapter 3, we classify all the 2-connected (n, n + 4)-graphs wit h at least four triangles . In Chapter 4 , we classify all the 2-connected (n, n + 4)-graphs wit h t hree triangles and one induced 4-cycle. In Chapter 5, we classify all the 2-connected (n, n + 4)graphs with three triangles and at least two induced 4-cycles . In each chapter, we obtain new families of chromatically unique graphs and chromatically equivalent graphs. We end the thesis by classifying all the 2-connected (n, n + 4)-graphs with exactly three triangles. We also determine the chromatic polynomial of all these graphs. The determination of the chromaticity of most classes of these graphs is left as an open problem for future research.